Students' Perception on EFL Speaking Skill Development - Nazara, Situjuh (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2011)
This paper is based on a study conducted in December 2010 to investigate the perceptions of the students of the English Teaching Study Program of FKIP-UKI Jakarta on their English speaking skill development. The findings revealed that all respondents viewed speaking important and they were willing to deal with the necessities to master it. Although they got interesting materials, empowering activities, and proper opportunity to practice speaking, they insisted to have longer time to practice. In addition, some respondents tended to avoid speaking due to their fear of lecturers’ ‘scolding’ and classmates’ laughing. The paper concludes by suggesting the need to create a friendly and conducive environment in the classroom.